Layer-by-layer aided β-cyclodextrin nanofilm for precise organic solvent nanofiltration - Li, Xin (2022)
Synthetic interlayers with multiple functions and structural stability have a high potential to construct novel thin film composite (TFC) membranes with demanding permselective property for precise separations. Herein, a functional interlayer derived from the polyelectrolyte-based layer-by-layer (LBL) self-assembly is reported to prepare interlayer engineered organic solvent nanofiltration (OSN) membranes using β-cyclodextrin (β-CD) as a monomer via interfacial polymerization (IP) process. Compared to the interlayer-free OSN membrane, a smoother selective layer with higher crosslinking degree is obtained for our developed membranes, enabling an improved organic dye rejection (e.g., 91.9% for methyl orange and 98.8% for brilliant blue R). Importantly, the LBL-aided β-CD nanofilm exhibits competitive permeances towards both polar (e.g., methanol, 5.8 LMH/bar) and nonpolar solvents (e.g., hexane, 7.0 LMH/bar). These performances can be attributed to the multiple roles of LBL-based interlayer as preventing the intrusion of selective layer and creating dual linkages (i.e., amide and ester), along with tailoring the physicochemical properties of caped β-CD nanofilm. Besides, the newly developed OSN membrane can discriminate between dye molecules with similar molecular weights and same charge but different molecular configurations. Meanwhile, its good structural integrity and long-term stability are also demonstrated by the 7-day filtration test using tetracycline in methanol and β-carotene in hexane, respectively, as evidence of constant solute rejections (≥90%) during the entire filtration process. This work unravels the functions of LBL-based interlayer in enhancing the OSN performance, offering new insights into shaping the development of interlayer engineered OSN membranes for real-life applications.